Injuries in Dutch elite field hockey players: A prospective cohort study - Delfino Barboza, S.; Nauta, J.; van der Pols, M. J.; van Mechelen, W.; Verhagen, E. A. L. M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
This study describes the prevalence, incidence density, severity, and nature of injuries in elite field hockey players over the Dutch 2015-2016 season. Eighty players answered a baseline questionnaire and were subsequently followed up every 2 weeks to report the hours spent on training/competition and experienced injuries, which were registered using the Oslo Sports Trauma Research Centre Questionnaire on Health Problems. Of the 74 players included in the analysis, 52 (70%) reported 112 injuries. Eighty-seven injuries (78%) received medical attention, and 56 (50%) led to training/competition time-loss. Thirty-four injuries (30%) hampered players` availability to train and compete. Most of the injuries (74%) were not caused by any contact. The mean prevalence of injury was 29% (95% confidence interval [CI] 3-55) for all, 9% (95% CI 0-20) for acute, and 14% (95% CI 0-36) for overuse injuries. Players sustained 3.5 (95% CI 2.5-4.5) new acute injuries per 1000 hours of training and 12.3 (95% CI 7.6-17.0) per 1000 hours of competition. The median of the severity score was 28 from 100 (25%-75% interquartile range [IQR] 16-42) for all, 35 (IQR 23-53) for acute, and 21 (IQR 16-31) for overuse injuries. On average, 1 in 4 elite field hockey players experiences an injury within a 2-week period during the season. Although acute injuries are common, overuse injuries pose a comparable problem in elite field hockey. As injuries are a burden on players` health and may hamper performance and availability to train and compete, prevention is of great importance.